Influence of Coarse Mg3Bi2 Particles on Deformation Behaviors of Mg-Bi Alloys - Guo, Tingting; Lu, Xuerong; Varma, Ramesh Kumar; Zhao, Cheng; Wang, Jun; You, Jianwei; Chen, Jian (Frontiers in Materials, 2021)
Mg-Bi binary alloys with concentration of 1, 3, 6 and 9 wt.% Bi and ternary Mg-9Bi-2.5Zn alloy were prepared by casting and hot extrusion. The results show that alloying with Bi refined as-cast grains of Mg alloys and the refinement efficiency of Bi is in between Al and Zr. It was also found that a critical value for the area fraction of constituent Mg3Bi2 particles seems to appear, which influences the dynamic recrystallization mechanism during extrusion. This influence results in either uniform or heterogenetic distribution of grain size and different extrusion texture intensities. Furthermore, the addition of Zn affected both the grain size and the area fraction/size of Mg3Bi2. Mechanical results and microstructure/fractography observation suggest that Mg3Bi2 particles do not impact the tensile nor compression yielding stress, but act as fracture sources.